Epidemiological, Morphological, and Morphometric Study on Haemonchus spp. Recovered From Goats in Egypt - Gareh, Ahmed; Elhawary, Nagwa M.; Tahoun, Amin; Ramez, Amany M.; EL-shewehy, Dina M. M.; Elbaz, Elzahara; Khalifa, Marwa I.; Alsharif, Khalaf F.; Khalifa, Refaat M. A.; Dyab, Ahmed K.; Monib, Mohmed Elsalahy M.; Arafa, Mohsen I.; et al. (Frontiers in Veterinary Science, 2021)
Goats can be infected by multiple groups of external and internal parasites. Haemonchus spp. are among abomasal parasites that can result in higher mortality and several considerable economic losses in goats. Early detection of parasites and better understanding of the major risk factors associated with infection are among the main strategies for controlling the infection. Considering this, information on haemonchosis in goats from Egypt and the contribution of goats in the maintenance of the epidemiological foci of the disease is limited. This study investigated the prevalence of Haemonchus species among 240 abomasum samples collected during postmortem examination of goat carcasses from Assiut Governorate, Egypt. Moreover, the association of the major risk factors to describe the epidemiological pattern of the disease was explored. This study demonstrated that 16.66% of abomasa samples harbored Haemonchus species. Additionally, age, sex, and sampling season were the most significant risk factors associated with infection. Following the variable factors under study, goats aged 1 year or older were at higher risk, with an infection rate of 22.14% (31 of 140), than those younger than 1 year (9%) (P= 0.008; odds ratio (OR) = 2.87; 95% confidence interval (CI), 1.30 to 6.35). The infection rate was 25% (19 of 76) in males and 12.8% (21 of 164) in females (P= 0.024; odds ratio (OR) = 2.26; 95% confidence interval (CI), 1.13 to 4.53). Moreover, the exposure to infection was higher in summer (22.22%) than that in winter (8.33%) (P= 0.007; odds ratio (OR) = 0.318; 95% confidence interval (CI), 0.139 to 0.725). More importantly, three species of the parasite—Haemonchus contortus, Haemonchus placei, and Haemonchus longistipes—were identified for the first time, and the confirmation of the identification and morphological characterization of the worms was performed using light microscopy and SEM. Collectively, this study reveals interesting epidemiological, morphological, and morphometric findings associated with the occurrence of haemonchosis among goats in Egypt. This study suggests further research for exploring the major circulating species of the parasite in Egypt, which is mandatory for controlling the disease.